Toxicity of zoledronic acid after intravenous administration: A retrospective study of 95 dogs. (3rd December 2021) - Brewer, David John; Macfarlane, Michael; O'Connell, Erin; Bacon, Nicholas J.
Abstract: Background: There is a paucity of veterinary literature on the safety or outcome of zoledronic acid (ZA) use in dogs for either bone pain or hypercalcemia. Hypothesis/Objectives: The primary aim was to report the adverse events in dogs receiving intravenous administration of ZA. Animals: Ninety‐five dogs with ZA use. Methods: A retrospective cohort study was performed; all dogs that received at least 1 dose of ZA and had a serum biochemistry profile performed before and after treatment were reviewed. Diagnosis, indication for treatment, adverse events and survival times were recorded. Results: Ninety‐five dogs met the inclusion criteria. Thirty‐one (33%) received multiple intravenous infusions of ZA (range, 2‐7), making a total of 166 administrations in all dogs. The dose range was 0.13 to 0.32 mg/kg, given at intervals of 4 to 6 weeks. Thirteen adverse events were recorded in 10 dogs: azotemia (n = 8), vomiting (n = 2), pancreatitis (n = 1), cutaneous ulceration (n = 1), and diarrhea (n = 1). Zoledronic acid could not be confirmed as the cause of azotemia in any case. The change in serum creatinine concentration from dose to dose was not related to the total dose received ( P  = .46). Five dogs (5%) changed Veterinary Comparative Oncology Group Common Terminology Criteria (VCOG‐CTAE) renal/genitourinary grade after administration of ZA; their total dose 0.4 mg/kg (range, 0.26‐0.66) was not significantly different to the group which did not change VCOG‐CTAE renal/genitourinary grade 0.35 mg/kg (range, 0.2‐1.50; P  = .93). Conclusions and Clinical Importance: Multiple doses of ZA were well tolerated in dogs within this study. A small number of dogs developed progressive azotemia which was not associated with cumulative dose.